Socio-thermal Analysis of Pawon Gebulen Kraton Yogyakarta - Nurina Vidya Ayuningtyas; Desy Ayu Krisna Murti; Istiana Adianti (Departement of Architecture, Universitas Islam Indonesia, 2021)
Architecture is a part of spatial planning that is very closely related to the culture that surrounds the community. One of the most interesting things is digging up information about the architecture of the Yogyakarta Palace. There are so many parts of the architectural layout of the palace that are very interesting to be thoroughly explained. One of the interesting things is Pawon. The research method used is a combination of measurements or direct observations in the field with software simulations. The results of this study are able to conclude that the thermal comfort in the Pawon Gebulen Kraton Yogyakarta building has not been fulfilled. The determining factors of thermal comfort discovered in this research are the relationship with the temperature and heat due to the heat transfer of natural lighting into the building. Even though it has not been fulfilled, the Abdi Dalem still voluntarily work in that place. This is because the social spirit of the community is quite high and the spirit of serving the Sultan is quite strong.Keywords: kitchen; kraton; light; pawon; temperature; thermal